Diseño e implementación de un laboratorio de sistemas digitales en la Universidad Técnica de Cotopaxi sede La Maná del cantón la maná provincia de cotopaxi, año 2013 - Figueroa Pincay, Armando Xavier (2015)
This research with the theme "Design and Implementation of a laboratory of digital systems in the Technical University of Cotopaxi La Maná Canton province of Cotopaxi, 2013" A digital communications system that can transmit a lot of information between equipment, increasing the transmission capacity of the currently installed systems, allowed to determine importance of the implementation of laboratories to improve the training of professionals who are trained in this center of higher education, to gather information was necessary to use technical survey aimed at students of the race.